Analisis Pengaruh Literasi Keuangan, Risiko, Psikologi Investasi, dan Media Sosial terhadap Minat Berinvestasi pada Saham Syariah - Yusuf Satrio Ratmojoyo (2021)
This study aims to analyze the effect of financial literacy, risk, investment psychology, and social media on the investment interest of the people of Jakarta in Islamic stocks. The sample used in this study uses 100 people who will represent the entire population. Data collection in this study was carried out using a questionnaire distributed by purposive sampling technique. The statistical methods used are descriptive statistical analysis, classical assumptions, multiple linear regression, validity and reliability, and hypotheses using SPSS Statistics 23 application as a data processor. The results of this study are the influence of the independent variables simultaneously on the interest in investing in Islamic stocks. However, in a partial test, only Financial Literacy, Risk, and Investment Psychology factors have a significant influence on interest in investing in Islamic stocks, while Social Media factors do not have a significant influence on interest in investing in Islamic stocks.